Morphogenesis of the sexual phase of seven epiphitic taxa of Polypodium (Polypodiaceae) from Mexico - Vázquez-Pérez, Nancy; Mendoza-Ruiz, Aniceto; Pérez-García, Blanca (Instituto de Ecología, A.C., 2014)
Morphology of the sexual phase of seven epiphytic taxa of Polypodium that grow in Mexico was observed and described. The spores of all species studied are monolete, ellipsoid to reniform, and verrucate to tuberculate. All the species analyzed have the Vittaria-type pattern of germination. In regard to the prothallial development, the Drynaria-type was observed in Polypodium furfuraceum, P. plebeium, P. polypodioidesvar. aciculare, P. polypodioides var. polypodioides, whereas P. rhodopleuron. P. fraternum and P. lepidotrichum displayed the Aspidium-type pattern. Unisexual and/or bisexual gametophytes were observed in some species. Polypodium fraternum, P. furfuraceum, P. lepidotrichum, P. plebeium, P. polypodioides var. aciculare and P. polypodioides var. polypodioides developed archegonial gametophytes while P. rhodopleuron, P. plebeium and P. polypodioides var. polypodioides formed antheridial gametophytes. A trend to the vegetative propagation of the gametophytes was observed in P. lepidotrichum and P. rhodopleuron.